Hydroxytyrosol Improves Obesity and Insulin Resistance by Modulating Gut Microbiota in High-Fat Diet-Induced Obese Mice - Liu, Zhuoqun; Wang, Ningning; Ma, Yanan; Wen, Deliang (Frontiers in Microbiology, 2019)
Systemic low-grade inflammation and intestinal dysfunction are thought to be associated with obesity and insulin resistance. Hydroxytyrosol (HT) may reduce obesity and insulin resistance (IR) in high-fat diet (HFD)-fed mice. However, the mechanism by which HT reduces obesity and insulin resistance is still unknown. In this study, we found that HT gavage for 8 weeks altered the intestinal microbiota, maintained intestinal barrier function, reduced endotoxin release into the blood, mitigated the inflammation level and lipid accumulation in liver, reduced obesity, and alleviated IR via the JNK/IRS (Ser 307) pathway in HFD mice. The beneficial effects of HT were also transferable through fecal microbiota transplantation. Our data indicate that HT can improve obesity and insulin resistance by altering the composition of the intestinal microbiota.